Pricing and Quality Improvement Decisions in the End-of-Life Vehicle Closed-Loop Supply Chain Considering Collection Quality - Zhou F.; Chen T.; Tiwari S.; Si D.; Pratap S.; Mahto R.V. (My University, 2025)
This article investigates the effects of end-of-life vehicle (ELV) collection quality on pricing and quality improvement decisions for different recycling modes by considering the discrepant heterogeneity of ELVs due to individual utilization and component degradation. This article examines the pricing and quality improvement decisions within an ELV closed-loop supply chain with heterogeneous collection quality that includes one manufacturer and one retailer. Stackelberg game models are formulated to examine the equilibrium solution in relation to three recycling modes (ELVs are recycled by the manufacturer, retailer, and third-party). We study the pricing and quality improvement decisions of ELV recycling to probe the influential mechanism of ELV collection quality under different recycling scenarios. The numerical experiment provides empirical guidance for ELV recycling management practices. Results show that wholesale and retail prices decrease with increasing ELV collection quality. In addition, there is a positive correlation between collection quality and the overall performance of the ELV supply chain. This article enhances better understanding on pricing and quality improvement decision-making in relation to ELV collection quality and helps participants in the closed-loop supply chain to determine the best recycling mode. © 1988-2012 IEEE.